Detection and quantification of phytic acid in black pepper variety Panniyur-1 using Polyacrylamide Gel Electrophoresis - Giridhari, A.C.; Sujatha, R.; Deeshma, K.P. (Journal of Tropical Agriculture, 2017)
Inositol hexakisphosphate (InsP6), commonly called phytic acid is a major phosphorus store in plants. It has important functions in germination and growth of seedlings and also help in plant defence against various biotic as well as abiotic stresses. The quantity of InsP6 is estimated commonly by tedious procedures like HPLC, NMR spectroscopy, TLC etc. Some of these methods also involve the use of harmful radioactive elements. Polyacrylamide gel electrophoresis (PAGE) is a rather easier and simpler method for the estimation of phytate in plant sample. PAGE was used to detect and quantify InsP6 in leaf tissues of black pepper variety Panniyur1. Crude extract of Panniyur1 leaf tissue and different concentrations of the commercially available phytate standards were prepared and analysed using PAGE. Standard curve was plotted using the band intensities (volume) (y-axis) and concentrations of phytate standard (x-axis). The estimated quantity of phytate in the sample based on standard curve was 620 nmolesg-1 fresh weight of leaf tissue.